2010
DOI: 10.1007/s10826-010-9355-x
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking and Internal Obstacles to Receiving Support in the Wake of Community Violence Exposure: The Case of Arab and Jewish Adolescents in Israel

Abstract: We examined help-seeking and internal obstacles to receiving psychosocial support in the wake of community violence exposure in a sample of 1,835 Arab and Jewish adolescents living in Israel. Paper and pencil surveys conducted in schools examined adolescents' personal victimization and witnessing of community violence in the past year, and then queried adolescents about their help-seeking after violence exposure. Our findings indicated widespread exposure to community violence, par

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Other studies carried out in Israel have found that more Israeli Arab than Jewish adolescents reported their intention to seek help from teachers and educational counselors [13], and more Israeli Arab adolescents exposed to frequent and severe acts of violence requested help from a mental health professional [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies carried out in Israel have found that more Israeli Arab than Jewish adolescents reported their intention to seek help from teachers and educational counselors [13], and more Israeli Arab adolescents exposed to frequent and severe acts of violence requested help from a mental health professional [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Of the limited research available where racial and ethnic differences are explored in adolescents, CVE and psychological distress are found to differ across racial and ethnic subgroups (Stein, Jaycox, Katoaoka, Rhodes, & Vestal, ). For example, African American and Latino adolescents were found to be significantly more likely to witness violence compared with Caucasian adolescents independent of socioeconomic status (Crouch, Hanson, Saunders, Kilpatrick, & Resnick, ), and Arab adolescents in Israel were significantly more likely to have experienced CVE (both witnessed and through personal victimization) and to have been exposed to more severe types of violence (e.g., witnessing murder; being shot and wounded) compared with Jewish adolescents (Guterman, Haj‐Yahia, Vorhies, Ismayilova, & Leshem, ).…”
mentioning
confidence: 99%
“…Interestingly, Palestinian boys living in Israel reported higher helpseeking rates than girls (Guterman et al, 2010). Similar help seeking patterns by Palestinians from different environments could imply the involvement of socio-cultural factors, an assumption supported by previous findings, suggesting that Palestinians are more open to seeking mental health care than other Arab populations (Al-Krenawi et al, 2009).…”
Section: Gender Differences In Help Seeking Ratesmentioning
confidence: 59%
“…Seeking help conforms to the female social stereotype that includes dependence and emotional expression (Eagly, 2009), while men are expected to be self-dependent and seeking help could threat their masculinity (Galdas, Cheater, & Marshall, 2005). Gender roles and stereotypes are culture dependent, and can account for the variations in the effect of gender on help seeking in different cultures (Guterman, Haj-Yahia, Vorhies, Ismayilova, & Leshem, 2010;Sherer & Karnieli-Miller, 2007). Seeking mental help carries the stigma of shame, and the fear of stigma is very potent among Arabs due to cultural sensitivity, explaining the reluctance of Arab of both genders to seek formal help (Al-Krenawi & Graham, 2000;Al-Krenawi et al, 2009).…”
Section: Gendermentioning
confidence: 99%